A PKD1L3 splicing variant in taste buds is not cleaved at the G protein-coupled receptor proteolytic site - Kashyap, Parul (Biochem Biophys Res Commun, 2019)
Mutations in polycystin proteins PKD1 and TRPP2 lead to autosomal dominant polycystic kidney disease. These two proteins form a receptor-ion channel complex on primary cilia. PKD1 undergoes an autoproteolysis at the N terminal G-protein-coupled receptor proteolytic site (GPS), which is essential for the function of PKD1. Whether GPS cleavage happens in other PKD proteins and its functional consequence has remained elusive. Here we studied the GPS cleavage of PKD1L3, a protein that associates with TRPP3 in taste cells and may play a role in sour taste. Our results show that PKD1L3 also undergoes GPS cleavage. Mutation at the GPS abolishes the cleavage, and the non-cleavable mutant does not traffic to the plasma membrane when associated with TRPP3. We also found that a splicing variant of PKD1L3, which was originally identified in taste buds, is not cleaved. Amino acids L708 and S709, which are missing in this splicing variant, are crucial for the GPS cleavage of PKD1L3 and the trafficking of the PKD1L3/TRPP3 complex. Our results gain insight into the molecular mechanism of the GPS cleavage of PKD1L3. The presence of the non-cleavable variant suggests the potential in vivo function of uncleaved PKD proteins.